Writing Intergenerational Female Relationships: Ann Radcliffe’s The Romance of the Forest (1791) - Irving, Roslyn Joy (FOCUS: Papers in English Literary and Cultural Studies, 2024)
This article uses The Romance of the Forest (1791) as a case study on the ways Radcliffe writes intergenerational female relationships and engages with the limitations of sensibility and “good” conduct. It will demonstrate how Radcliffe both criticises and endorses female sensibility, as an action which leads to poor judgement and as a tool to manage relationships, as seen in the case of Madame La Motte. It will also address Radcliffe’s framing of the doctrines of conduct literature, which produce an admirable role model in the form of Madame La Luc, who is subsequently written out of the text. Finally, it makes a case for intergenerational exchange where the process of a mother-daughter education gives the young women in the novel patterns of behaviours to reshape. This article contributes to the growing volume of research on Radcliffe’s politically engaged writing and the Female Gothic.